Urban Inclusiveness and Perception of Class Mobility - From the Perspective of Floating Population - Marco Desogu; Elisa Casu (Multidisciplinary Journal of Akseprin Indonesia, 2023)
Improving people's sense of happiness and gain is the meaning of the title of inclusive city construction. Paying attention to the individual's subjective perception of class mobility can promote the orderly mobility of social classes and promote social structural changes. Based on the data of China Labor-force Dynamic Survey (CLDS) in 2016, this paper empirically analyzes the impact of urban inclusion on class mobility by using the Ordered Probit model. The results show that the probability of intra-generational upward mobility perception increases by 0.0897 and the probability of inter-generational upward mobility perception increases by 0.0617 for each unit of urban inclusion. This result is still robust after removing extreme values and changing the definition of perceived class mobility. Considering the endogeneity of urban inclusion, this paper uses Conditional Mixed Process (CMP) estimation to effectively reduce the bias caused by Ordered Probit model estimation. Further mechanism analysis shows that urban inclusion can positively affect the social network of floating population and then affect their sense of class mobility. Heterogeneity analysis found that the positive impact of urban inclusiveness on the perception of class mobility was the largest in the central region and the floating population of agricultural household registration type. Therefore, the relevant national departments still need to introduce some policies, pay attention to the accumulation of human capital, and continuously enhance the upward mobility perception of the eastern and western regions and non-agricultural Hukou groups while improving the urban inclusiveness, so as to enhance their "sense of access".